Proceedings of the 36th European Conference on Cognitive Ergonomics 2018
DOI: 10.1145/3232078.3232085
|View full text |Cite
|
Sign up to set email alerts
|

Mild Place Illusion

Abstract: Developments in Virtual Reality (VR) technology have modified the creative potential of each individual. We introduce a new concept, called "mild place illusion", as a new paradigm for designing VR-based user interfaces targeted at stimulating creativity. We show that for creative tasks -such as creative writing, new product ideation, and brainstorming -a "just-enough" amount of place illusion leads to a greater self-perception of creativity, as opposed to a "full-level" place illusion. This is a somewhat unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The mild place illusion condition resulted in a higher self-perception of creativity in comparison to the full level of place illusion condition and condition without illusion. Moreover, they verified that a mild place illusion interface enabled individuals to generate higher levels of creativity and performance (Gonçalves and Campos, 2018).…”
Section: Interfacementioning
confidence: 72%
See 3 more Smart Citations
“…The mild place illusion condition resulted in a higher self-perception of creativity in comparison to the full level of place illusion condition and condition without illusion. Moreover, they verified that a mild place illusion interface enabled individuals to generate higher levels of creativity and performance (Gonçalves and Campos, 2018).…”
Section: Interfacementioning
confidence: 72%
“…Four main types of research experiments are used to evaluate the impact of using VR in brainstorming to enhance creativity, according to our literature analysis. (1) Approximately 33% of the studies either designed an interface or developed an application to further test and compare the effectiveness of the application for brainstorming (Fominykh et al, 2014;Forens et al, 2015;Gonçalves and Campos, 2018;Kuťák et al, 2019;Petrykowski et al, 2019). (2) Approximately 26.7% of the papers compared specific elements in VEs, such as the different virtual objects (Minas et al, 2016) or dynamic and static persona (Bonnardel et al, 2016).…”
Section: Research Trends and Samplementioning
confidence: 99%
See 2 more Smart Citations
“…In terms of creativity enhancement, are multiple senses better than one? In the area of creativity support tools, Goncalves and Campos [68] demonstrated that a creative writing support software with both audio (inspirational soundtrack) and visual (dynamic landscape) stimuli promoted greater self-reported creativity compared to using a baseline text processor without any audiovisual accompaniments. Interestingly, the authors found that a "just enough" approach providing audiovisual stimuli within the software itself was at least as good, if not better, at promoting creativity than a full-on virtual reality environment.…”
Section: Multisensory Influences On Creativitymentioning
confidence: 99%